Business Enterprise and Globalization: Towards a Transnational Business History. Issue 3 (24th August 2017) - Boon, Marten
Abstract : Transnational history emerged strongly as globalization intensified in the 1990s, questioning national historiographies and creating new research agendas. Business history has not been part of this, but recent calls within the field to engage more visibly and authoritatively with debates on the history of globalization warrant a closer inspection of transnational history. The article draws on key concepts from transnational history and discusses their application in the work of, among others, Sven Beckert, Jessica Lepler, Stephanie Decker, Ray Stokes, and Michael Miller. The article argues that transnational history provides opportunities to increase business history's engagement with the history of globalization.